D-dimer Levels as Novel Biomarker Predictor for All-cause Inhospital Mortality Risk in COVID-19 Patients - Nisa Amnifolia Niazta; Muchammad Dzikrul Haq Karimullah; William Sulistyono Putra; Norma Khoirun Nisa'; Phamella Esty Nuraini; Shaffan Ula Prasetya (Heart Science Journal, 2021)
BACKGROUND: COVID-19 has infected the world on a wide spectrum, from mild to severe and causing death. As of January 1st 2021, global case fatality rate (CFR) was 2.2 % due to COVID-19. CFR in Kediri district is 7.7 %, higher than Nasional CFR which is only 3 %. We analysed elevated D-dimer as one of predictor inhospital mortality in COVID-19OBJECTIVES: To determine the association and evaluate the optimal cut off point D-dimer level as predictor for all-cause inhospital mortality of COVID-19 patients.METHODS: This is a single center cross sectional. A total of 185 COVID-19 patients confirmed positive by RT-PCR were hospitalized at Kediri General Hospital since March to December 2020 met the inclusion criteria. D-dimer levels were categorized into 2 groups, above and below the cut of point. We analyzed 4 cut of points, D-dimer ≥ 0.5 µg/ml, D-dimer ≥ 2 µg/ml, D-dimer ≥ 3 µg/ml, and D-dimer ≥ 4 µg/ml. The primary endpoint was all-cause inhospital mortality. Data were collected retrospectively and processed using SPSS version 25.0.RESULTS:During hospitalization, 45 patients (24.3%) were died. Elevated D-dimer ≥ 4 µg/ml was statistically significant associated with all-cause inhospital mortality (adjusted OR95%CI = 3.46 [1.41 – 8.49], p = 0.007), with a sensitivity of 82.1% and a specificity of 42.2% (AUC, 0.628; 95% CI, 0.527 – 0.728, p = 0.012).CONCLUSION: Elevated D-dimer level were associated statistically significant with all-cause inhospital mortality. In our study, optimal cut of point D-dimer value was 4 µg/ml.